COVID-19: An Italian Hospital Response From the Nursing Perspective. Issue 2 (April 2021) - Rolandi, Stefano; Villa, Giulia; D'Aloia, Pasqualino; Gengo, Valentina; Negro, Alessandra; Manara, Duilio Fiorenzo
Abstract : Novel coronavirus disease-2019 (COVID-19) is a new respiratory disease that has spread widely throughout the world. On February 20, 2020, the first Italian case of COVID-19 was reported. The infection rapidly spread across the country, and by August 11, 2020, a total of 250 566 official cases with 32 205 deaths (12.8%) were reported in Italy, counting a total of 96 884 positive cases and 16 833 deaths (17.3%) in the Lombardy region only. A huge demand to handle the COVID-19 outbreak challenged both the health care providers and the ordinary work in the hospital. From the beginning of the crisis, San Raffaele Scientific Institute, a 1318-bed tertiary care university hospital located in Lombardy, Northern Italy, has played a major role in supporting the national health care system for the treatment of COVID-19 cases, and a significant reorganization of the hospital was immediately required. The reorganization was carried out both structurally and with regard to the distribution of medical and nonmedical staff. This article aims to highlight the management strategies for the health care staff subsequent to the pandemic intense workload in San Raffaele Scientific Institute.